The perspective of students on drivers and benefits of building information modelling incorporation into quantity surveying profession in Klang Valley Malaysia - Chai, Chai Lim; Tien, Choon Toh; Yoke, Lian Lew; Chin, Xian Lau; Chen Goh, Chen Goh; Masrom, Md Asrul Nasid; Zainordin, Nadzirah; Siaw, Chuing Loo (UMP Press, 2020)
Building Information Modelling (BIM) is a very useful tool that facilitates architecture, engineering and construction (AEC) professionals and stakeholders in planning, designing and constructing the buildings through 3D models. BIM can be widened to building operations and data storage which can be accessible by owners and others. Such data help owners and stakeholders to generate results according to the information gained through BIM models. The objectives of this study were to identify the perspective of students on drivers of BIM incorporation into the quantity surveying profession and to identify the perspective of students on benefits of BIM incorporation into the quantity surveying profession. A questionnaire survey was carried out to gain the students’ perspective on drivers and benefits of BIM incorporation into the quantity surveying profession in Klang Valley, Malaysia. Specifically, this study investigated twelve drivers and fourteen benefits of BIM incorporation into the quantity surveying profession. The top three drivers were improving the capacity to provide whole-life value to the client, desire for innovation to remain competitive and strong support from university management and industry. The top three benefits were BIM provides fast, effective and efficient quantity take-off and cost estimation, time savings in the preparation of estimating cost and improved visualization for better understanding of designs for measurement and minimise omissions. For future research, it is recommended that the study be replicated at other regions so that a clearer view of this topic can be obtained. Besides, qualitative research methods could be used in identifying other drivers and benefits not covered in this study. By answering the questions in the survey form, the students were able to gain some knowledge on BIM and its importance to the quantity surveying profession. Also, it would be interesting to include industrial practitioners in this kind of study, allowing comparisons of the results between academia and industry at a later stage. Nonetheless, this study benefited the undergraduate students pursuing the Bachelor of Science (Hons) Quantity Surveying programme, universities, colleges and other institutions that offered the quantity surveying programmes at various levels and quantity surveyors working in the construction industry by exposing them to a comprehensive list of drivers and benefits of BIM incorporation into quantity surveying profession. In a way, this study helped promoted BIM and its implementation in the field of quantity surveying in Klang Valley, Malaysia.